Investigating the gas-to-dust ratio in the protoplanetary disk of HD 142527. (14th October 2019) - Soon, Kang-Lou; Momose, Munetake; Muto, Takayuki; Tsukagoshi, Takashi; Kataoka, Akimasa; Hanawa, Tomoyuki; Fukagawa, Misato; Saigo, Kazuya; Shibai, Hiroshi
Abstract: We present ALMA observations of the 98.5 GHz dust continuum and the ^13COJ = 1 –0 and C^18OJ = 1 –0 line emissions of the protoplanetary disk associated with HD 142527. The 98.5 GHz continuum shows a strong azimuthal-asymmetric distribution similar to that of the previously reported 336 GHz continuum, with a peak emission in dust concentrated region in the north. The disk is optically thin in both the 98.5 GHz dust continuum and the C^18OJ = 1 –0 emissions. We derive the distributions of gas and dust surface densities, Σ _g and Σ _d, and the dust spectral opacity index, β, in the disk from ALMA Band 3 and Band 7 data. In the analyses, we assume the local thermodynamic equilibrium and the disk temperature to be equal to the peak brightness temperature of ^13CO J = 3 –2 with a continuum emission. The gas-to-dust ratio, G/D, varies azimuthally with a relation G/D Σ _d^-0.53, and β is derived to be ≈ 1 and ≈ 1.7 in the northern and southern regions of the disk, respectively. These results are consistent with the accumulation of larger dust grains in a higher pressure region. In addition, our results show that the peak Σ _d is located ahead of the peak Σ _g . If the latter corresponds to a vortex of high gas pressure, the results indicate that the dust is trapped ahead of the vortex, as predicted by some theoretical studies.